Efektivitas Pembentukan Belajar Mandiri Mahasiswa Baru S1 PGSD-UT Melalui Pelatihan Keterampilan Belajar Mandiri dan Tutorial dalam Peningkatan Kemampuan Penulisan Karya Ilmiah - Sulistiyono Sulistiyono; Barokah Widuroyekti (Autentik : Jurnal Pengembangan Pendidikan Dasar, 2020)
This study aims to: (1) obtain an overview of the effectiveness of the formation of independent learning through Independent Learning Activity Training in improving the ability of Scientific Writing at the PGSD-UT S1 Pokjar Pamekasan 2017-2018.2; (2) obtain an overview of the effectiveness of the formation of independent learning through designing tutorials in improving the ability of Scientific Writing at S1 PGSD-UT Pokjar Pamekasan 2017-2018.2. Based on these objectives, this research was carried out using a descriptive-qualitative research approach. The process of data analysis begins with examining all data, reducing data, arranging it in units, and analyzing it with percentages. The data analysis of the research was carried out by quantitative and qualitative analysis techniques. Quantitative data were analyzed using percentage calculations. This step is the first step towards the whole process of qualitative descriptive analysis. Quantitative descriptive data analysis in the form of a percentage will be the basis for determining the effectiveness of qualitative descriptive analysis of the variables studied. Analysis activities include: data reduction, data presentation, inference and verification. Data reduction activities include classification of data, coding of data according to the type of data. Data is presented in the form of a description. Followed by meaning and conclusion. Through the steps of the research, the research findings are as follows. First, research findings on the formation of independent learning through Independent Learning Activity Training in improving the ability of Scientific Writing at the PGSD-UT S1 Pokjar Pamekasan 2017-2018.2 achieve good quality scores and very effective mastery acquisition. Second, the research findings about the effectiveness of the formation of independent learning through designing tutorials in improving the ability of Scientific Writing at S1 PGSD-UT Pokjar Pamekasan 2017-2018.2 achieve good scores and effective acquisition of mastery. Third, students' scientific work achieves sufficient quality scores and effective mastery.